2010
DOI: 10.1063/1.3279786
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic separation of colorectal cancer cells

Abstract: Separation of colorectal cancer cells from other biological materials is important for stool-based diagnosis of colorectal cancer. In this paper, we use conventional dielectrophoresis in a microfluidic chip to manipulate and isolate HCT116 colorectal cancer cells. It is noticed that at a particular alternating current frequency band, the HCT116 cells are clearly deflected to a side channel from the main channel after the electric activation of an electrode pair. This motion caused by negative dielectrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 46 publications
0
77
0
Order By: Relevance
“…The throughput of the ApoStream device is faster as compared to other small microfluidic chip based DEP technologies. 19,22,32,45 A study by Hu et al showed a higher throughput of 10 000 cells per second, which is almost the twice the throughput of ApoStream device. However, that technology was limited to cell labeling.…”
Section: F Cell Viability Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The throughput of the ApoStream device is faster as compared to other small microfluidic chip based DEP technologies. 19,22,32,45 A study by Hu et al showed a higher throughput of 10 000 cells per second, which is almost the twice the throughput of ApoStream device. However, that technology was limited to cell labeling.…”
Section: F Cell Viability Studiesmentioning
confidence: 98%
“…For example, DEP has been used to separate colorectal cancer cell lines in a microfluidic chip. 22 Contactless DEP microfluidic device was utilized to study the behavior of mouse ovarian cells. 23 Human cervical carcinoma cell line HeLa was concentrated using circular microelectrodes.…”
mentioning
confidence: 99%
“…DEP testing can be used to measure these properties, allowing it to be used as a characterisation tool DEP was first used on living cells by Pohl and Hawk in 1966 16 , but has since been used to both characterise and separate different populations of cells, for a variety of different purposes within biology and medicine, such as to study links between multidrug resistance and cancer, and to study apoptosis 17 . DEP has been employed in a micro-fluidic chip to separate colorectal cancer cells from E.coli bacteria and Human Embryonic Kidney 293 cells 18 . Dielectric methods have also been used to separate breast cancer cells from blood 19 , and to distinguish stem cells from their progeny 20 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, DEP has been used in blood analysis, 7 including characterization of human red blood cells based on the blood type, 8 sorting and concentrating the target microbe from a flowing blood sample, 9 and isolation of red blood cells affected by malaria. 10 By exploiting subtle differences between the healthy cells and their malignant counterparts, DEP can be employed to successfully isolate different cancerous cells 11 and separate them from healthy ones, 12 identify different types of cultured tumor cells, 13 quantify electric properties of drug-resistant breast cancer cells, 14 or study key stages in apoptosis of 1932-1058/2012/6(2)/024117/15/$30.00 V C 2012 American Institute of Physics 6, 024117-1 leukemia cells. 15 Close connection between electrical properties of biological cells and their physiological and metabolic properties is often exploited to separate viable from non-viable cells, 16,17 but it also makes DEP a useful tool in studying stem cells, [18][19][20] sorting out multiple different species of bacteria [21][22][23] and subpopulations within the same bacterial species, 24 or in characterizing plant protoplasts, yeast and algae.…”
Section: Introductionmentioning
confidence: 99%